CYP2U1: An emerging treatable neurometabolic disease with cerebral folate deficiency in 2 Chinese brothers - Sheila Suet-Na Wong; Liz Yuet-Ping Yuen; Elaine Kan; Nenad Blau; Richard Rodenburg; Ching-wan Lam; Virginia Chun-Nei Wong; Fanny Mochel; Ron A. Wevers; Cheuk-Wing Fung (Molecular Genetics and Metabolism Reports, 2024)
With the rapid advancement of medical technologies in genomic and molecular medicine, the number of treatable neurometabolic diseases is quickly expanding. Spastic paraplegia 56 (SPG56), one of the severe autosomal recessive forms of neurodegenerative disorders caused by pathogenic variants in the CYP2U1 gene, has no reported specific targeted treatment yet. Here we report 2 Chinese brothers with CYP2U1 bi-allelic pathogenic variants with cerebral folate deficiency who were treated for over a decade with folinic acid supplement. Patients have remained stable under therapy.